Helping the identification of refugee shipwreck victims in the Straits of Sicily: An AIM-Indel reference database for the Tigray population of Ethiopia. (December 2017) - Kumar, H.R.S.; Haddish, K.; Futwi, N.; Lacerenza, D.; Tewelemedhin, G.; Manukonda, R.V.; Di Gaetano, C.; Fondevila, M.; Phillips, C.; Robino, C.
Abstract: One of the worst accidents in the European refugee crises occurred on 18th April 2015, when a migrant vessel sank in the Straits of Sicily, with over 800 deaths, including 350 Eritreans. Ancestry informative markers (AIMs) can contribute to the ongoing DVI process enabling the matching of human remains and reference samples from victim's relatives according to their ancestry. A reference population dataset (n = 228) of 46 AIM Insertion Deletion polymorphisms (Indels), obtained from the Tigray population (the major ethnic group in Northern Ethiopia and Eritrea), proved to be effective at discriminating Tigray and other sub-Saharan African populations. Ancestry inference was also satisfactory in comparison to Middle East, when excluding Northern Africans from this population group, and Central-Southern Asia.